Aberrant methylation of tRNAs links cellular stress to neuro‐developmental disorders. (25th July 2014) - Blanco, Sandra; Dietmann, Sabine; Flores, Joana V; Hussain, Shobbir; Kutter, Claudia; Humphreys, Peter; Lukk, Margus; Lombard, Patrick; Treps, Lucas; Popis, Martyna; Kellner, Stefanie; Hölter, Sabine M; et al.
Abstract Mutations in the cytosine‐5 RNA methyltransferase NSun2 cause microcephaly and other neurological abnormalities in mice and human. How post‐transcriptional methylation contributes to the human disease is currently unknown. By comparing gene expression data with global cytosine‐5 RNA methylomes in patient fibroblasts and NSun2‐deficient mice, we find that loss of cytosine‐5 RNA methylation increases the angiogenin‐mediated endonucleolytic cleavage of transfer RNAs (tRNA) leading to an accumulation of 5′ tRNA‐derived small RNA fragments. Accumulation of 5′ tRNA fragments in the absence of NSun2 reduces protein translation rates and activates stress pathways leading to reduced cell size and increased apoptosis of cortical, hippocampal and striatal neurons. Mechanistically, we demonstrate that angiogenin binds with higher affinity to tRNAs lacking site‐specific NSun2‐mediated methylation and that the presence of 5′ tRNA fragments is sufficient and required to trigger cellular stress responses. Furthermore, the enhanced sensitivity of NSun2‐deficient brains to oxidative stress can be rescued through inhibition of angiogenin during embryogenesis. In conclusion, failure in NSun2‐mediated tRNA methylation contributes to human diseases via stress‐induced RNA cleavage.